English Dubs: Why are Anglophone Viewers Receptive to English Dubbing on Streaming Platforms and to Foreign-Accent Strategies? - Hayes, Lydia (Íkala, Revista de Lenguaje y Cultura, 2023)
Accents are often utilised in fictional audiovisual products to determine the creation of character identity. This is due to the set of cultural connotations typically associated with any given accent in any given language community. However, is there really one monolingual target audience anymore? In the age of streaming platforms, and at the rate the localisation industry is creating subtitles and revoiced versions, the target audience for many products has become multilingual. The English ‘dubbing revolution’, pioneered by streaming giant Netflix, perfectly depicts the broadening of target audiences in global distribution. The subject of this article is the popularly termed ‘foreignisation’ strategy, as it features in English dubs. The strategy is explored in relation to the novelty of (English) dubbing for most viewers as well as the ubiquity of foreign varieties of English in everyday life in the Anglosphere and, consequently, in English-language original fiction. Theoretical insights are also offered on the unique acceptance of English dubbing, in general, and of foreign accents as a dubbing strategy, in particular. The case of the Castilian-Spanish dubbing industry is also explored for contrastive purposes, elucidating the characteristics of (im)mature dubbing audiences: their habits, preferences, and (in)flexibility. The conclusions present a set of hypotheses drawn from the article’s discussion that provide plausible answers to the questions posed in the article’s title.